First evidence of genotype–phenotype correlations in Gorlin syndrome. Issue 8 (8th June 2017) - Evans, D Gareth; Oudit, Deemesh; Smith, Miriam J; Rutkowski, David; Allan, Ernest; Newman, William G; Lear, John T
Abstract : Background: Gorlin syndrome (GS) is an autosomal dominant syndrome characterised by multiple basal cell carcinomas (BCCs) and an increased risk of jaw cysts and early childhood medulloblastoma. Heterozygous germline variants in PTCH1 and SUFU encoding components of the Sonic hedgehog pathway explain the majority of cases. Here, we aimed to delineate genotype–phenotype correlations in GS. Methods: We assessed genetic and phenotypic data for 182 individuals meeting the diagnostic criteria for GS (median age: 47.1; IQR: 31.1–61.1). A total of 126 patients had a heterozygous pathogenic variant, 9 had SUFU pathogenic variants and 46 had no identified mutation. Results: Patients with variants were more likely to be diagnosed earlier (p=0.02), have jaw cysts (p=0.002) and have bifid ribs (p=0.003) or any skeletal abnormality (p=0.003) than patients with no identified mutation. Patients with a missense variant in PTCH1 were diagnosed later (p=0.03) and were less likely to develop at least 10 BCCs and jaw cysts than those with other pathogenic PTCH1 variants (p=0.03). Patients with SUFU pathogenic variants were significantly more likely than those with PTCH1 pathogenic variants to develop a medulloblastoma (p=0.009), a meningioma (p=0.02) or an ovarian fibroma (p=0.015), but were less likely to develop a jaw cyst (p=0.0004). Conclusion: We propose that the clinical heterogeneity of GS can in part be explained by the underlying or SUFU variant.